MASSIVE: a distributed virtual reality system incorporating spatial trading - Greenhalgh, C.; Benford, S. (Proceedings of 15th International Conference on Distributed Computing Systems, 1995)
MASSIVE is a distributed virtual reality system. It provides rich facilities to support user interaction and cooperation via text, audio and graphics media and interaction is controlled by a spatial model of interaction. The communications architecture is based on processes communicating via typed connections which have interfaces on both ends and which integrate RPCs, attributes and streams in a common context. A spatial interface trading service, the aura manager, has been developed to support interface trading in a spatial context. The concepts embodied in the aura manager can be useful in other interface trading situations, especially where notions of "space" and "meeting" may be applied.